2018
DOI: 10.3892/ijo.2018.4304
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SIRT6 by miR-34c-5p is associated with poor prognosis and promotes colon cancer proliferation through inhibiting apoptosis via the JAK2/STAT3 signaling pathway

Abstract: Sirtuin 6 (SIRT6) is a member of the nicotinamide adenine dinucleotide positivity-dependent class III deacetylase sirtuin family. The present study aimed to explore the expression and function of SIRT6 in colon cancer. Furthermore, the partial mechanism underlying the dysregulation of SIRT6 was investigated. The results of immunohistochemistry demonstrated that SIRT6 was markedly downregulated in colon cancer tissues, and patients with high SIRT6 expression had a better prognosis than those who did not. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…In the present study, SIRT5 overexpression was associated with a favorable prognosis in OC, and elevated SIRT5 levels in patients with clinical stage III+IV and TP53 mutations were associated with improved OS, implying that SIRT5 is a potential biomarker of OC. Previous studies referring to SIRT6 have investigated its role as a tumor suppressor, and its decreased expression is associated with poor OS in patients with pancreatic cancer (44), hepatic carcinoma (45) and colon cancer (46). The present study demonstrated that SIRT6 overexpression was associated with good prognosis in OC.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, SIRT5 overexpression was associated with a favorable prognosis in OC, and elevated SIRT5 levels in patients with clinical stage III+IV and TP53 mutations were associated with improved OS, implying that SIRT5 is a potential biomarker of OC. Previous studies referring to SIRT6 have investigated its role as a tumor suppressor, and its decreased expression is associated with poor OS in patients with pancreatic cancer (44), hepatic carcinoma (45) and colon cancer (46). The present study demonstrated that SIRT6 overexpression was associated with good prognosis in OC.…”
Section: Discussionsupporting
confidence: 65%
“…While miR-99a [20]and miR-21 [21] are highly expressed in osteosarcoma tissues and cells, down-regulation of their expression inhibits osteosarcoma cell proliferation, invasion and metastasis, and promotes apoptosis. Interestingly, miR-34c-5p functions as a carcinogen in various cancers, such as colon cancer [22] and bladder cancer [23]. However, increasing evidence indicates that miR-34c-5p acts as a tumor suppressor in various tumors, such as acute myeloid leukemia [24].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the miR-30 family, miR-504, miR-34c, miR-488, miR-15b, miR-195, miR-497, miR-15a, miR-503, miR-141, miR-182, miR-96, and miR-136 were also related to invasion, proliferation, metastasis and tumor growth, or survival of several cancers including CRC. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] However, there are few studies on the role of included prioritized miRNAs for interactions with obesity. For obesity there are some studies on mice, for instance, miR-16-5p decrease with high weight and a mutation in miR-16 gene lead to increasing in body weight.…”
Section: F I G U R Ementioning
confidence: 99%